Restarting the conversation: challenges at the interface between ecology and society. Issue 6 (1st August 2010) - Groffman, Peter M; Stylinski, Cathlyn; Nisbet, Matthew C; Duarte, Carlos M; Jordan, Rebecca; Burgin, Amy; Previtali, M Andrea; Coloso, James
Abstract : The exchange of information between researchers, resource managers, decision makers, and the general public has long been recognized as a critical need in environmental science. We examine the challenges in using ecological knowledge to inform society and to change societal actions, and identify a set of options and strategies to enhance this exchange. Our objectives are to provide background information on societal knowledge and interest in science and environmental issues, to describe how different components of society obtain information and develop their interests and values, and to present a framework for evaluating and improving communication between science and society. Our analysis strongly suggests that the interface between science and society can only be improved with renewed dedication to public outreach and a wholesale reconsideration of the way that scientists communicate with society. Ecologists need to adopt new models of engagement with their audiences, frame their results in ways that are more meaningful to these audiences, and use new communication tools, capable of reaching large and diverse target groups.